Judicialization of access to medicines and pharmaceutical policies in latin american countries - Vargas Peláez, Claudia Marcela (2016)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Ciências da Saúde, Programa de Pós-Graduação em Farmácia, Florianópolis, 2016.